The effects of melatonin on ischemia-reperfusion induced changes in rat corpus cavernosum - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2002)
Purposes: We determined the change in contractile activity and oxidant damage after ischemia-reperfusion of rat corpus cavernosum and investigated the effects of melatonin (Sigma Chemical Co., St. Louis, Missouri) on these parameters. Materials and Methods: The abdominal aorta of male Wistar albino rats was occluded to induce ischemia-reperfusion. Melatonin (10 mg./kg.) or vehicle (1%, alcohol in saline per kg.) was administered subcutaneously before ischemia-reperfusion. In the sham operated control group the abdominal aorta was left intact and the rats were treated with melatonin or vehicle. After decapitation corporeal tissues were placed in organ baths or stored for biochemical measurements. Results: In sham operated rats phenylephrine added cumulatively caused a concentration dependent contraction in corpus cavernosum strips precontracted with KCl and acetylcholine added cumulatively to strips precontracted with phenylephrine caused a dose dependent relaxation response. In the ischemia-reperfusion group contraction and relaxation responses decreased significantly compared within controls. Melatonin treatment in the ischemia-reperfusion group reversed these responses. Myeloperoxidase activity and the lipid peroxidation level of the corporeal tissues in the ischemia-reperfusion group were significantly higher than in the sham operated control group. Melatonin treatment in the ischemia-reperfusion group decreased myeloperoxidase activity and the lipid peroxidation level compared with ischemia-reperfusion alone, whereas melatonin treatment alone had no significant effect on these parameters. Conclusions: In this study the corporeal tissues of rats exposed to ischemia-reperfusion had lower responses to contractile and relaxant agents than those of sham operated rats. Treatment with melatonin before ischemia-reperfusion almost completely reversed smooth muscle responses and prevented the increased myeloperoxidase activity and lipid peroxidation of corporeal tissues.
Keywords: penis; rats, Wistar; melatonin; reperfusion injury; muscle, smooth; ENDOTHELIAL DYSFUNCTION; ANTIOXIDANT ACTIVITY; MYOCARDIAL-ISCHEMIA; LIPID-PEROXIDATION; TISSUE-INJURY; BRAIN-REGIONS